Correlates of Physical Activity and Sedentary Behaviour of Academic and Non-Academic Staff in University of Ilorin, Ilorin, Nigeria - Adebayo Babatunde Samson; Mercy Adedamola Agboola (Indonesian Journal of Multidiciplinary Research, 2022)
This study examined the correlates of physical activity and sedentary behavior of academic and non-academic staff at the University of Ilorin. The descriptive research design of the survey method was used for the study. The population comprised academic and non-academic staff of the University of Ilorin. 142 selected through random sampling techniques were used for the study. The research instrument was a structured questionnaire validated by three experts in the field of Human Kinetics Education, University of Ilorin. Descriptive inferential statistics of Pearson Product Moment Correlation (PPMC) was used for the study. The findings revealed that age, gender; work schedule, and health status were significant correlates of physical activity and sedentary lifestyle of academic and non-academic staff. The study recommended that the University of Ilorin management should encourage her staff by working with experts to develop a program that will address the inadequacies in physical activity participation among the staff. Furthermore, the University of Ilorin staff should take advantage of the institutions’ sports facilities to increase participation in physical activities and exercise.